Behavioral and Thermoregulatory Responses to Changes in Ambient Temperature and Wheel Running Availability in Octodon degus - Bano-Otalora, Beatriz; Rol, Maria Angeles; Madrid, Juan Antonio (Frontiers in Integrative Neuroscience, 2021)
Octodon degus is primarily a diurnal species, however, in laboratory conditions, it can switch from diurnal to nocturnal in response to wheel running availability. It has been proposed that this activity inversion obeys thermoregulatory constraints induced by vigorous physical exercise. Thus, its activity shifts to the night as the ambient temperature is lower.Here, we investigate the relationship between thermoregulation and the activity phase-inversion in response to wheel-running in this species. We measured behavioral activity and body temperature rhythms in diurnal naïve animals under 12 h light: 12 h dark cycles at four different ambient temperatures (spanning from 26°C to 32°C), and following access to running wheels while maintained under high ambient temperature.Our results show that naïve degus do not shift their diurnal activity and body temperature rhythms to a nocturnal phase when subjected to sequential increases in ambient temperature. However, when they were provided with wheels under constant high-temperature conditions, all animals inverted their diurnal phase preference becoming nocturnal. Both, negative masking by light and entrainment to the dark phase appeared involved in the nocturnalism of these animals. Analysis of the thermoregulatory response to wheel running revealed some differences between masked and entrained nocturnal chronotypes.These data highlight the importance of the coupling between wheel running availability and ambient temperature in the nocturnalism of the degus. The results support the view that an innate “protective” pre-program mechanism (associating darkness and lower ambient temperature) may change the timing of behavioral activity in this species to reduce the potential risk of hyperthermia.